A kind of wiring harness cement and preparation method thereof

By combining high molecular weight polyisobutylene and functional additive particles, a dense three-dimensional network is formed, which solves the problems of insufficient sealing, adhesion and aging resistance of wire harness putty, and achieves a better protection effect for automotive wire harnesses.

CN118755447BActive Publication Date: 2025-01-14KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411253321.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-14
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Existing wire harness putty has shortcomings in terms of sealing performance, adhesion, workability and aging resistance, which affects its application effect in automotive wire harness protection.

Method used

A compounding scheme of high molecular weight polyisobutylene, functional polyisobutylene, and functional additive particles is adopted to form a dense three-dimensional molecular chain connection network through chemical reaction, which enhances the sealing and adhesion of the putty, and improves the waterproofness and aging resistance through the surface structure of the functional additive particles.

Benefits of technology

It significantly improves the sealing, adhesion, workability and aging resistance of wire harness putty, reduces oil seepage, stickiness and aging embrittlement, and enhances the overall performance of automotive wire harness protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of cement, and in particular to a wiring harness cement and a preparation method thereof. The wiring harness cement, in parts by mass, comprises the following raw materials: 5 to 20 parts of high molecular weight polyisobutylene, 5 to 25 parts of functional polyisobutylene, 5 to 15 parts of silicone oil, 1 to 5 parts of functional resin, 0.2 to 1 part of antioxidant, 0.2 to 1 part of lubricant, 40 to 80 parts of filler, 3 to 10 parts of pigment, 0.01 to 0.4 parts of inhibitor, 0.1 to 0.8 parts of catalyst, and 8 to 15 parts of functional additive. The automotive wiring harness cement prepared in the present application not only retains good cement waterproofness, adhesion and thermal stability, but also can greatly increase the sealing, stickiness, operability and aging resistance of the cement during use on this basis, greatly reducing the oil seepage, stickiness and aging embrittlement of the cement during actual application, and has excellent application prospects in the automotive field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of adhesive putty, and in particular to a wiring harness adhesive putty and a preparation method thereof. Background Art

[0002] The automotive wiring harness is a whole that provides service equipment for the load source group, such as the central control harness, high-voltage harness, engine harness, etc. Its main function is to facilitate installation and maintenance, and ensure that electrical equipment can work under the worst conditions, thereby combining a variety of wires of different specifications, colors and functions into one, and bundling the wires into bundles with insulating materials.

[0003] In order to protect the automotive wiring harness, especially to improve its overall waterproof performance, automotive wiring harness putty is needed; as a special material to protect the internal wiring harness of the car, wiring harness putty not only needs to have good waterproof properties, but also needs to ensure that the wires and cables are not damaged by external forces to a certain extent, and maintain the wiring harness with good electrical properties. Therefore, the performance requirements for wiring harness putty have become more and more diversified with the continuous development of the automotive industry.

[0004] With the continuous development of automotive electronics, the wiring harnesses in cars are becoming more and more complex, and the protection and insulation of the wiring harnesses have become more important. The wiring harness glue has gained more and more applications and gradually replaced plastic sleeves due to its advantages of strong plasticity and good adhesion. However, as the application of glue products continues to deepen, technical problems in the application of glue are also exposed. For example, the sealing, stickiness, operability and aging resistance of the glue have greatly affected the quality of the glue in practical applications and the size of the applicable environment.

[0005] Therefore, in order to solve the above problems, the present application provides a wiring harness putty for automobiles and a preparation method thereof. The wiring harness putty prepared in the present application not only maintains good waterproofness, adhesion and thermal stability of the putty, but also can greatly increase the sealing, stickiness, operability and aging resistance of the putty during use on this basis, and greatly reduces the oil seepage, stickiness and aging embrittlement of the putty during actual application, and has very excellent application prospects in the automotive field. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a wiring harness putty, the raw materials of which are, by mass: 5 to 20 parts of high molecular weight polyisobutylene, 5 to 25 parts of functional polyisobutylene, 5 to 15 parts of silicone oil, 1 to 5 parts of functional resin, 0.2 to 1 part of antioxidant, 0.2 to 1 part of lubricant, 40 to 80 parts of filler, 3 to 10 parts of pigment, 0.01 to 0.4 parts of inhibitor, 0.1 to 0.8 parts of catalyst, and 8 to 15 parts of functional additive.

[0007] As a preferred solution, the mass ratio of the high molecular weight polyisobutylene, the functional polyisobutylene and the functional additive is (5-18): (5-15): (9-13).

[0008] As a preferred solution, the mass ratio of the high molecular weight polyisobutylene, the functional polyisobutylene and the functional additive is (7-15): (5-12): (10-12).

[0009] As a preferred solution, the mass ratio of the high molecular weight polyisobutylene to the filler is (5-18): (60-70).

[0010] As a preferred solution, the mass ratio of the high molecular weight polyisobutylene to the functional resin is (5-18): (2-3).

[0011] As a preferred solution, the weight average molecular weight of the high molecular weight polyisobutylene is 500,000 to 1,000,000 Da.

[0012] As a preferred solution, the weight average molecular weight of the high molecular weight polyisobutylene is 700,000 to 850,000 Da.

[0013] As a preferred solution, the functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene.

[0014] As a preferred solution, the mass ratio of the highly active polyisobutylene to the inactive liquid polyisobutylene is (5-12):(1-2).

[0015] As a preferred solution, the mass ratio of the highly active polyisobutylene to the inactive liquid polyisobutylene is (5-10):(1-1.5).

[0016] As a preferred solution, the highly active polyisobutylene is monovinyl-terminated polyisobutylene.

[0017] As a preferred solution, the number average molecular weight of the highly active polyisobutylene is 1000-2500 Da.

[0018] As a preferred solution, the number average molecular weight of the highly active polyisobutylene is 1000-2300 Da.

[0019] As a preferred solution, the Alpha double bonds of the highly active polyisobutylene account for ≥85%.

[0020] As a preferred solution, the terminal group of the inactive liquid polyisobutylene does not contain an Alpha double bond.

[0021] As a preferred solution, the number average molecular weight of the inactive liquid polyisobutylene is 1000-2000 Da.

[0022] As a preferred solution, the number average molecular weight of the inactive liquid polyisobutylene is 1100-1500 Da.

[0023] The above-mentioned compound polyisobutylene scheme added in the present application can ensure that the wiring harness glue has good insulation, waterproofness and adhesion, while greatly improving its sealing, adhesion and aging resistance and other properties, and has good operability. The present application adds high-activity polyisobutylene and inactive liquid polyisobutylene as functional polyisobutylene to the glue system, which can greatly enhance the density of the glue system. The added high-activity polyisobutylene contains a large number of active Alpha double bonds that can continuously form a bonding connection with the high molecular weight polyisobutylene through chemical reaction during the formation and use of the glue, thereby forming an extremely dense and complex three-dimensional molecular chain connection network in the colloidal system, so that in the long-term use process, not only the glue has excellent continuous bonding performance, but also the migration rate of water molecules, active molecules and free groups in the system can be greatly reduced, thereby greatly reducing the probability of mutual contact between them, thereby greatly enhancing the aging resistance of the glue during use, and greatly increasing the free resistance and penetration path length of water molecules in the system, thereby obtaining excellent waterproof, bonding / adhesion and aging resistance and other properties.

[0024] On the other hand, the added inactive liquid polyisobutylene can serve as the initial carrier of the functional auxiliary agent particles added in the present application during the preparation of the cement, and can easily form a layered membrane structure on the surface of the particles, reducing the aggregation phenomenon during the kneading process, and can quickly carry the functional auxiliary agent particles to fuse with the highly active polyisobutylene, and then through the reaction and connection between the highly active polyisobutylene and the active groups on the surface of the functional particles, the highly active polyisobutylene is used as an active carrier of the functional auxiliary agent particles, thereby greatly enhancing the dispersion effect of the functional auxiliary agent particles in the high viscosity system of high molecular weight polyisobutylene, and the dense three-dimensional network formed by the reaction of the active polyisobutylene can greatly enhance the pore fixation of the functional auxiliary agent particles and other filler particles, reducing the subsequent particle migration and segregation phenomenon, thereby ensuring the overall performance of the cement such as overall insulation, waterproofness, aging resistance and adhesion.

[0025] As a preferred solution, the silicone oil is hydrogen-containing silicone oil.

[0026] As a preferred solution, the hydrogen content of the hydrogen-containing silicone oil is 0.05-0.2wt%.

[0027] As a preferred solution, the hydrogen content of the hydrogen-containing silicone oil is 0.07-0.1wt%.

[0028] As a preferred solution, the functional resin is hydrogenated petroleum resin.

[0029] As a preferred solution, the hydrogenated petroleum resin is hydrogenated C5 resin.

[0030] As a preferred solution, the softening point of the hydrogenated petroleum resin is 95-105°C.

[0031] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant 1024, and antioxidant 1330.

[0032] As a preferred solution, the lubricant is at least one of stearic acid, oleic acid, palmitic acid, ethyl stearate, stearic acid amide, and caproic acid amide.

[0033] As a preferred solution, the lubricant is a combination of stearic acid and ethyl stearate.

[0034] As a preferred embodiment, the mass ratio of stearic acid to ethyl stearate is (4-5): (1-2).

[0035] As a preferred solution, the filler is a combination of light calcium carbonate and heavy calcium carbonate.

[0036] As a preferred solution, the mass ratio of light calcium carbonate to heavy calcium carbonate is (28-34):(35-40).

[0037] As a preferred solution, the mass ratio of light calcium carbonate to heavy calcium carbonate is (30-32):(36-38).

[0038] As a preferred solution, the average particle size of the light calcium carbonate is 1500~2000 mesh.

[0039] As a preferred solution, the oil absorption value of the light calcium carbonate is 20-35 mL / 100 g.

[0040] As a preferred solution, the average particle size of the heavy calcium carbonate is 1000-1400 mesh.

[0041] As a preferred solution, the pigment is at least one of carbon black, titanium dioxide, iron oxide, phthalocyanine blue and chrome yellow.

[0042] As a preferred solution, the pigment is carbon black or titanium dioxide.

[0043] As a preferred solution, the inhibitor is at least one of alkynol inhibitors.

[0044] As a preferred solution, the inhibitor is 1-ethynylcyclohexanol.

[0045] As a preferred solution, the catalyst is a platinum catalyst or an organotin catalyst.

[0046] As a preferred solution, the catalyst is a platinum catalyst.

[0047] As a preferred solution, the functional additive is a modified composite particle.

[0048] As a preferred solution, the preparation method of the modified composite particles comprises the following steps: S1: adding silica, succinic anhydride and n-butyl titanate to deionized water, heating to 60-65°C, keeping the temperature for reaction for 2.5-3h, centrifuging the product, and drying it under vacuum at 65-70°C to obtain pretreated particles; S2: adding the pretreated particles, aluminum nitrate and hydrofluoric acid to deionized water, stirring at 35-40°C until there is no precipitation, adding to a reactor, heating to 70-80°C, keeping the temperature for 3-4h, and adding A deionized water solution containing terephthalic acid; S3: Control the pressure in the reactor to 2-2.2 MPa, heat to 190-210°C and keep warm for reaction for 12-16 hours. After the reaction is completed, centrifuge and filter the product, wash it with ethanol and deionized water for 2-3 times, and dry it to obtain a pre-product. Add the pre-product into deionized water again, add ammonia water to adjust the pH to 9-9.5, add tetraethyl orthosilicate and isopropanol, heat to 60-65°C and keep warm for reaction for 2-3 hours. After completion, centrifuge and filter the product, wash it with ethanol for 2-3 times, and dry it to obtain the product.

[0049] As a preferred solution, the mass ratio of silicon dioxide, succinic anhydride and n-butyl titanate is (1-1.5): (0.6-0.8): (0.1-0.2).

[0050] As a preferred solution, the average particle size of the silicon dioxide is 10-30 nm.

[0051] As a preferred solution, the mass ratio of the pretreated particles, aluminum nitrate, terephthalic acid and hydrofluoric acid is (0.8-1.2): (2-2.4): (1.4-1.8): (5-8).

[0052] As a preferred solution, the mass ratio of the pre-product, tetraethyl orthosilicate and isopropyl alcohol is (4-5): (0.5-0.6): (0.2-0.3).

[0053] As a preferred solution, the average particle size of the modified composite particles is 560-660 nm.

[0054] The functional additive particles added in this application can greatly improve the waterproofness, thermal stability, mechanical properties and aging resistance of the wiring harness glue. First, the composite structure of the silicon oxide particles wrapped in the framework particles formed by the functional additive particles added in this application can greatly increase the number of its surface active groups, so it can not only play a good role in dispersion within the system through interaction with highly active polyisobutylene, but also its strong system connection with polyisobutylene greatly enhances the upper limit of internal stress tolerance, so it can provide excellent connection and support when external forces act, thereby improving the mechanical properties of the glue when in use.

[0055] Secondly, the spherical structure formed by the functional additive particles can accelerate the aggregation of water molecules in the cement system through the rapid guidance of water molecules by surface groups in the cement system, and adsorb water molecules through the framework particle structure inside the composite particles, thereby effectively removing the water molecules inside the cement, and no desorption phenomenon will occur when used at a limited temperature, thereby greatly increasing the penetration resistance of water molecules inside the cement system. On the surface of the cement, its complex surface structure can cause the cement to form a high-roughness surface structure, thereby greatly reducing the surface energy and weakening the aggregation rate of water molecules on the surface of the cement. The water accumulated on the surface forms a continuous hydration layer structure, thereby obtaining an excellent waterproof and water-repellent effect.

[0056] Finally, the nano-particle pores formed by the functional additive particles in the cement system can greatly increase the steric hindrance between active molecular chains and molecules, thereby hindering the effective contact of active reaction groups, and thus helping to enhance the impedance of active reactions within the cement, thereby enabling the cement to have excellent aging resistance and maintain good continuous adhesion stability during the long-term use cycle of the cement.

[0057] The second aspect of the present application provides a method for preparing the above-mentioned wiring harness putty, which specifically includes the following steps: first, stir the functional polyisobutylene and the functional additive in a mixing container at a speed of 100-150rpm for 30-40min, mix them evenly and set them aside, then add all the raw materials except the catalyst into a kneader, heat them to 90-100℃ and start kneading for 1-2h, until there are no particles after kneading, naturally cool them to 60-70℃, add the catalyst and continue kneading for 30-40min to stir evenly, then heat them to 110-120℃ and continue kneading for 10-15min, and after completion, discharge the materials to obtain the wiring harness putty.

[0058] The beneficial effects of this application are:

[0059] 1. The wiring harness putty provided in the present application not only maintains good waterproofness, adhesion and thermal stability of the putty, but also can greatly increase the sealing, stickiness, operability and aging resistance of the putty during use on this basis, and greatly reduces the oil seepage, stickiness and aging embrittlement of the putty during actual application, and has very excellent application prospects in the automotive field.

[0060] 2. A wiring harness putty provided in the present application can ensure that the wiring harness putty has good insulation, waterproofness and adhesion, while greatly improving its sealing, adhesion and aging resistance and other properties by adding a compounded polyisobutylene solution, and has good operability; high-activity polyisobutylene and inactive liquid polyisobutylene are added to the putty system as functional polyisobutylenes, which can greatly enhance the density of the putty system. The added high-activity polyisobutylene contains a large number of active alpha double bonds that can continuously form bonding connections with high molecular weight polyisobutylene through chemical reactions during the formation and use of the putty, thereby forming an extremely dense and complex three-dimensional molecular chain connection network in the colloidal system, thereby not only maintaining the excellent continuous bonding performance of the putty during long-term use, but also greatly reducing the movement rate of water molecules, active molecules and free groups in the system.

[0061] 3. A wiring harness putty provided in the present application, in which the added inactive liquid polyisobutylene can serve as the initial carrier of the functional auxiliary agent particles added in the present application during the preparation process of the putty, and can easily form a layered film structure on the surface of the particles, reducing the aggregation phenomenon during the kneading process, and can quickly carry the functional auxiliary agent particles to fuse with the highly active polyisobutylene, and then through the reaction and connection between the highly active polyisobutylene and the active groups on the surface of the functional particles, the highly active polyisobutylene is used as an active carrier of the functional auxiliary agent particles, thereby greatly enhancing the dispersion effect of the functional auxiliary agent particles in the high viscosity system of the high molecular weight polyisobutylene, and the dense three-dimensional network formed by the reaction of the active polyisobutylene can greatly enhance the pore fixation of the functional auxiliary agent particles and other filler particles, reducing the subsequent particle migration and segregation phenomenon, thereby ensuring the overall performance of the putty such as overall insulation, waterproofness, aging resistance and adhesion.

[0062] 4. A wiring harness putty provided in the present application, the added functional auxiliary agent particles can greatly improve the waterproofness, thermal stability, mechanical properties and aging resistance of the wiring harness putty; the composite structure of the framework particles wrapped by the silica particles formed by the functional auxiliary agent particles can greatly enhance the number of its surface active groups, so that it can not only play a good dispersion role in the system through the interaction with the highly active polyisobutylene, but also its strong system connection force with polyisobutylene greatly enhances the upper limit of the internal stress tolerance; the spherical structure formed by the functional auxiliary agent particles can accelerate the aggregation of water molecules in the putty system through the rapid guidance of water molecules by the surface groups in the putty system, and adsorb water molecules through the framework particle structure inside the composite particles, thereby effectively removing the water molecules inside the putty, and no desorption phenomenon will occur when used at a limited temperature, thereby greatly increasing the penetration resistance of water molecules in the putty system, thereby obtaining excellent waterproofness. DETAILED DESCRIPTION

[0063] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0064] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0065] Example 1

[0066] Example 1 The first aspect provides a wiring harness putty, the raw materials of which are, by mass, 7 parts of high molecular weight polyisobutylene, 9 parts of functional polyisobutylene, 10 parts of silicone oil, 2 parts of functional resin, 0.5 parts of antioxidant, 0.6 parts of lubricant, 68 parts of filler, 4 parts of pigment, 0.02 parts of inhibitor, 0.1 parts of catalyst and 11.5 parts of functional additive.

[0067] The high molecular weight polyisobutylene has a weight average molecular weight of 800,000 Da and is purchased from BASF as a BASF Oppanol B80 product.

[0068] The functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene, and the mass ratio of the two is 8:1.

[0069] The highly active polyisobutylene is a monovinyl terminated polyisobutylene with a number average molecular weight of 1000 Da and an Alpha double bond ratio of 89.2%. It was purchased from BASF under the model number BASF HRPIB1000.

[0070] The terminal group of the inactive liquid polyisobutylene does not contain an Alpha double bond, and the number average molecular weight of the inactive liquid polyisobutylene is 1200 Da. The product is purchased from the Hongrui HRD-13 model sold by Shandong Hongrui Petrochemical Co., Ltd.

[0071] The silicone oil is hydrogen-containing silicone oil with a hydrogen content of 0.07 wt %, and is purchased from the RH-DH07 end-hydrogen-containing silicone oil product sold by Runhe Materials Company.

[0072] The functional resin is hydrogenated C5 resin with a softening point of 100°C, and is purchased from Lanzhou Petrochemical Company and is a product of model LH100-0.

[0073] The antioxidant is antioxidant 1010.

[0074] The lubricant is a composition of stearic acid and ethyl stearate, and the mass ratio of the two is 5:1.

[0075] The filler is a composition of light calcium carbonate and heavy calcium carbonate, and the mass ratio of the two is 30:38.

[0076] The light calcium carbonate had an average particle size of 1600 mesh and an oil absorption value of 28 mL / 100 g, and was purchased from Changzhou Calcium Carbonate Model 503.

[0077] The average particle size of heavy calcium carbonate was 1200 mesh, and it was purchased from Shanghai Hangchi Heavy Calcium Carbonate Model 110.

[0078] The pigment is titanium dioxide, purchased from DuPont Ti-Pure R-960.

[0079] The inhibitor was 1-ethynylcyclohexanol, purchased from Beiteli, model HJC-01.

[0080] The catalyst is a platinum catalyst, purchased from Shanghai Sibao Advanced Materials Co., Ltd., model ACS-Pt-3000, with a platinum content of 3000 ppm.

[0081] The functional additive is a modified composite particle. The preparation method of the modified composite particle comprises the following steps, calculated by mass: S1: 1.2 parts of silicon dioxide, 0.75 parts of succinic anhydride and 0.16 parts of n-butyl titanate are mixed and added to 100 parts of deionized water, the temperature is raised to 65°C, the product is centrifuged and filtered after being kept warm for 3 hours, and vacuum dried at 65°C to obtain pretreated particles; S2: 0.96 parts of pretreated particles, 2.2 parts of aluminum nitrate and 7.8 parts of hydrofluoric acid are added to 80 parts of deionized water, stirred at 40°C until there is no precipitation, added to a reactor, and the temperature is raised to 75°C and kept warm for 3 hours. After 5 hours, a deionized water solution containing 1.72 parts of terephthalic acid (a total of 15 parts) was added; S3: the pressure in the reactor was controlled to 2.1 MPa, the temperature was raised to 205°C and the reaction was kept warm for 13.5 hours. After the reaction was completed, the product was centrifuged and filtered, washed with ethanol and deionized water for 3 times and dried to obtain a pre-product. 4.8 parts of the pre-product were added to 80 parts of deionized water again, ammonia water was added to adjust the pH to 9.4, 0.56 parts of tetraethyl orthosilicate and 0.28 parts of isopropanol were added, the temperature was raised to 62°C and the reaction was kept warm for 2.5 hours. After completion, the product was centrifuged and filtered, washed with ethanol 3 times, and dried to obtain the product.

[0082] The average particle size of silica was 16 nm.

[0083] The average particle size of the modified composite particles was 612 nm.

[0084] The second aspect of Example 1 provides a method for preparing wiring harness adhesive, which specifically includes the following steps: first, stir the functional polyisobutylene and the functional additive in a mixing container at a speed of 120 rpm for 35 minutes, mix them evenly and set them aside, then add all the raw materials except the catalyst into a kneader, heat it to 95°C and start kneading for 1 hour, until there are no particles after kneading, naturally cool it to 65°C, add the catalyst and continue kneading for 35 minutes to stir evenly, then heat it to 110°C and continue kneading for 10 minutes, and discharge the material after completion to obtain the wiring harness adhesive.

[0085] Example 2

[0086] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the wiring harness putty, in parts by mass, are: 12 parts of high molecular weight polyisobutylene, 8 parts of functional polyisobutylene, 6 parts of silicone oil, 2 parts of functional resin, 0.5 parts of antioxidant, 0.6 parts of lubricant, 68 parts of filler, 4 parts of pigment, 0.02 parts of inhibitor, 0.1 parts of catalyst, and 11.5 parts of functional additives.

[0087] The functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene, and the mass ratio of the two is 7:1.

[0088] Example 3

[0089] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the wiring harness putty, in parts by mass, are: 10 parts of high molecular weight polyisobutylene, 11 parts of functional polyisobutylene, 5 parts of silicone oil, 2 parts of functional resin, 0.5 parts of antioxidant, 0.6 parts of lubricant, 68 parts of filler, 4 parts of pigment, 0.02 parts of inhibitor, 0.1 parts of catalyst, and 11.5 parts of functional additives.

[0090] The functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene, and the mass ratio of the two is 10:1.

[0091] Example 4

[0092] The specific implementation of this embodiment is basically the same as that of Example 1, with the only difference being that the raw materials of the wiring harness putty, in parts by mass, are: 15 parts of high molecular weight polyisobutylene, 6 parts of functional polyisobutylene, 5 parts of silicone oil, 2 parts of functional resin, 0.5 parts of antioxidant, 0.6 parts of lubricant, 68 parts of filler, 4 parts of pigment, 0.02 parts of inhibitor, 0.1 parts of catalyst, and 11.5 parts of functional additives.

[0093] The functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene, and the mass ratio of the two is 5:1.

[0094] Comparative Example 1

[0095] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene, and the mass ratio of the two is 2:1.

[0096] Comparative Example 2

[0097] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene, and the mass ratio of the two is 1.5:5.

[0098] Comparative Example 3

[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that the silicone oil is methyl-terminated polydimethylsilane with a viscosity of 200 cSt and a temperature of 25° C., purchased from WACKER AK100 sold by WACKER in Germany.

[0100] Comparative Example 4

[0101] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the wiring harness putty, in parts by mass, are: 20 parts of high molecular weight polyisobutylene, 3.5 parts of functional polyisobutylene, 10 parts of silicone oil, 2 parts of functional resin, 0.5 parts of antioxidant, 0.6 parts of lubricant, 68 parts of filler, 4 parts of pigment, 0.02 parts of inhibitor, 0.1 parts of catalyst, and 11.5 parts of functional additives.

[0102] Comparative Example 5

[0103] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the raw materials of the wiring harness putty, in parts by mass, are: 11 parts of high molecular weight polyisobutylene, 12 parts of functional polyisobutylene, 10 parts of silicone oil, 2 parts of functional resin, 0.5 parts of antioxidant, 0.6 parts of lubricant, 68 parts of filler, 4 parts of pigment, 0.02 parts of inhibitor, 0.1 parts of catalyst, and 4.5 parts of functional additives.

[0104] Comparative Example 6

[0105] The specific implementation of this comparative example is basically the same as that of Example 1, except that the high-activity polyisobutylene is a monovinyl-terminated polyisobutylene with a number average molecular weight of 3300 Da and an Alpha double bond ratio of 71.6%, which is purchased from the corresponding monovinyl-terminated polyisobutylene product sold by BASF.

[0106] Comparative Example 7

[0107] The specific implementation of this comparative example is basically the same as that of Example 1, except that: instead of using inactive liquid polyisobutylene, ordinary liquid polyisobutylene is used instead, the end group contains an Alpha double bond, and its number average molecular weight is 2400Da, and the PB2400 model product is purchased from Jinan Shuangying Chemical Co., Ltd.

[0108] Comparative Example 8

[0109] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional additive is a modified composite particle, and the preparation method of the modified composite particle comprises the following steps, calculated by mass: S1: 3.8 parts of silicon dioxide, 0.45 parts of succinic anhydride and 0.08 parts of n-butyl titanate are mixed and added to 80 parts of deionized water, the temperature is raised to 65°C, and the product is centrifuged and filtered after the reaction is kept warm for 3 hours, and vacuum dried at 65°C to obtain pretreated particles; S2: 2.1 parts of pretreated particles, 2.2 parts of aluminum nitrate and 7.8 parts of hydrofluoric acid are added to 80 parts of deionized water, stirred at 40°C until there is no precipitation, and then added to the reaction mixture. In the kettle, the temperature was raised to 75°C and kept warm for 3.5 hours, and then a deionized water solution containing 1.72 parts of terephthalic acid (a total of 15 parts) was added; S3: the pressure in the reactor was controlled to be 2.1MPa, the temperature was raised to 205°C and kept warm for 13.5 hours. After the reaction was completed, the product was centrifuged and filtered, washed with ethanol and deionized water for 3 times and dried to obtain a pre-product. 4.8 parts of the pre-product were added to 80 parts of deionized water again, ammonia water was added to adjust the pH to 9.4, 0.56 parts of tetraethyl orthosilicate and 0.28 parts of isopropanol were added, the temperature was raised to 62°C and kept warm for 2.5 hours. After completion, the product was centrifuged and filtered, washed with ethanol 3 times, and dried to obtain the product.

[0110] The average particle size of the modified composite particles is 743 nm.

[0111] Comparative Example 9

[0112] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional additive is a modified composite particle, and the preparation method of the modified composite particle comprises the following steps, calculated by mass: S1: 1.2 parts of silicon dioxide, 0.75 parts of succinic anhydride and 0.16 parts of n-butyl titanate are mixed and added to 100 parts of deionized water, the temperature is raised to 65°C, the product is centrifuged and filtered after the reaction is kept warm for 3 hours, and vacuum dried at 65°C to obtain pretreated particles; S2: 0.55 parts of pretreated particles, 3.8 parts of aluminum nitrate and 15.6 parts of hydrofluoric acid are added to 100 parts of deionized water, stirred at 40°C until there is no precipitation, and then added Put it into the reactor, heat it to 75℃ and keep it warm for 3.5h, then add a deionized water solution containing 4.2 parts of terephthalic acid (20 parts in total); S3: control the pressure in the reactor to 2.1MPa, heat it to 205℃ and keep it warm for 13.5h. After the reaction is completed, centrifuge and filter the product, wash it with ethanol and deionized water for 3 times and dry it to obtain a pre-product. 4.8 parts of the pre-product are added to 80 parts of deionized water again, ammonia water is added to adjust the pH to 9.4, 0.56 parts of tetraethyl orthosilicate and 0.28 parts of isopropanol are added, heat it to 62℃ and keep it warm for 2.5h. After completion, centrifuge and filter the product, wash it with ethanol 3 times and dry it to obtain it.

[0113] The average particle size of the modified composite particles is 808 nm.

[0114] Performance Evaluation

[0115] The corresponding performance tests were carried out on the mortars prepared in the examples and comparative examples. The test standards are shown in Table 1. The comparative examples and examples adopted the same standards. The test results of the examples and comparative examples are recorded in Tables 1 and 2, respectively.

[0116] The manual kneading property, water resistance and aging resistance were tested according to the following methods and conditions.

[0117] Manual kneading property: The clay obtained in the examples and comparative examples was made into samples with a size of 50 mm × 25 mm × 2 mm. (1) Five points were evenly selected on the surface of the sample and the surface of the sample clay was gently touched with fingers. The fingers could easily leave the surface of the clay after contacting it, and there was no obvious residue attached to the fingers on the surface of the clay. (2) The clay sample was observed to have a smooth and dry surface appearance, without obvious sticky material seepage or adhesion, and no obvious clay wire drawing phenomenon. If the above requirements (1) and (2) were met at the same time, the manual kneading property was qualified, otherwise it was unqualified. The sample pass rate results were recorded in Tables 1 and 2.

[0118] Waterproof property: The clay obtained in the embodiment and the comparative example was made into a sample with a size of 50 mm × 25 mm × 2 mm, and placed in a constant temperature water tank at 40°C, 75% relative humidity, and with the water surface 100 mm away from the top of the sample for 240 h. After being taken out, it was immediately bent 180° in the horizontal direction and wrapped around a plastic round rod with a diameter of 2 mm. The surface state was observed. If it could be flexibly attached to the round rod without obvious brittleness, cracking, blistering and depression, it was recorded as qualified. On the contrary, if it could not be flexibly attached to the round rod and any obvious brittleness, cracking, blistering and depression occurred, it was recorded as unqualified. 50 samples were tested in each group, and the qualified rate of the samples was recorded in Tables 1 and 2.

[0119] Aging resistance: The mortar prepared in the examples and comparative examples was placed in an oven at 150°C for 240h, taken out and cooled to room temperature, and then made into a sample with a size of 25mm×12.5mm×2mm. The sample was pasted on a PP plate with a width of 25mm, with a bonding size of 25mm×12.5mm. A substrate of the same size was pasted on the other side, and rolled back and forth 3 times with a 2kg roller. After being placed at (23±2)°C and (50±5)%RH for 5min, the peel strength after aging treatment was tested by the peel strength method. If the strength after the test can retain more than 90% (including 90%) of the original peel strength, it is considered qualified, otherwise it is unqualified. The qualified rate of the samples is recorded in Tables 1 and 2.

[0120]

[0121]

[0122] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 to 4 of the present application have obvious advantages over Comparative Examples 1 to 9 in terms of mechanical properties, waterproof properties, sealing properties, thermal stability and aging resistance. This is mainly due to the combined effect of the functional polyisobutylene and functional auxiliary agent particles and other compounded raw material solutions specified in the present application. Comparative Examples 1 to 9 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A wiring harness mastic, characterized in that: The raw materials are as follows, by mass: 5-20 parts of high molecular weight polyisobutylene, 5-25 parts of functional polyisobutylene, 5-15 parts of silicone oil, 1-5 parts of functional resin, 0.2-1 parts of antioxidant, 0.2-1 parts of lubricant, 40-80 parts of filler, 3-10 parts of pigment, 0.01-0.4 parts of inhibitor, 0.1-0.8 parts of catalyst, and 8-15 parts of functional additive; The weight average molecular weight of the high molecular weight polyisobutylene is 500,000 to 1,000,000 Da; The functional polyisobutylene is a composition of highly active polyisobutylene and inactive liquid polyisobutylene; the mass ratio of the highly active polyisobutylene to the inactive liquid polyisobutylene is (5-12): (1-2); The highly active polyisobutylene is monovinyl terminated polyisobutylene; The number average molecular weight of the highly active polyisobutylene is 1000-2500 Da; The Alpha double bond ratio of the highly active polyisobutylene is ≥85%; The terminal groups of the inactive liquid polyisobutylene do not contain alpha double bonds; The number average molecular weight of the inactive liquid polyisobutylene is 1000-2000Da; The silicone oil is hydrogen-containing silicone oil; The functional resin is hydrogenated petroleum resin; The lubricant is at least one of stearic acid, oleic acid, palmitic acid, ethyl stearate, stearic acid amide, and caproic acid amide; The functional additive is a modified composite particle; The preparation method of the modified composite particles comprises the following steps: S1: adding silica, succinic anhydride and n-butyl titanate to deionized water, heating to 60-65° C., keeping the temperature for reaction for 2.5-3 hours, centrifuging and filtering the product, and vacuum drying at 65-70° C. to obtain pretreated particles; S2: Add the pretreated particles, aluminum nitrate and hydrofluoric acid to deionized water, stir evenly at 35-40°C until there is no precipitation, add to the reactor, heat to 70-80°C and keep warm for 3-4 hours, then add the deionized water solution containing terephthalic acid; S3: Control the pressure in the reactor to 2-2.2MPa, heat to 190-210°C and keep warm for 12-16 hours, after the reaction is completed, centrifuge and filter the product, wash with ethanol and deionized water for 2-3 times, and dry to obtain the pre-product, add the pre-product to deionized water again, add ammonia water to adjust the pH to 9-9.5, add tetraethyl orthosilicate and isopropanol, heat to 60-65°C and keep warm for 2-3 hours, after completion, centrifuge and filter the product, wash with ethanol 2-3 times, and dry to obtain the product; The mass ratio of silicon dioxide, succinic anhydride and n-butyl titanate is (1-1.5): (0.6-0.8): (0.1-0.2); The mass ratio of the pretreated particles, aluminum nitrate, terephthalic acid and hydrofluoric acid is (0.8-1.2): (2-2.4): (1.4-1.8): (5-8); The mass ratio of the pre-product, tetraethyl orthosilicate and isopropyl alcohol is (4-5): (0.5-0.6): (0.2-0.3); The average particle size of the modified composite particles is 560-660 nm; The mass ratio of the high molecular weight polyisobutylene, the functional polyisobutylene and the functional additive is (5-18): (5-15): (9-13); The mass ratio of the high molecular weight polyisobutylene to the filler is (5-18): (60-70); The mass ratio of the high molecular weight polyisobutylene to the functional resin is (5-18): (2-3).

2. The wiring harness mastic according to claim 1, characterized in that: The hydrogen content of the hydrogen-containing silicone oil is 0.05-0.2 wt %.

3. The wiring harness mastic according to claim 2, characterized in that: The hydrogenated petroleum resin is hydrogenated C5 resin; the softening point of the hydrogenated petroleum resin is 95-105°C.

4. The wiring harness mastic according to claim 3, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant 1024, and antioxidant 1330.

5. The wiring harness mastic according to claim 4, characterized in that: The lubricant is a composition of stearic acid and ethyl stearate; the mass ratio of stearic acid to ethyl stearate is (4-5): (1-2).

6. The wiring harness mastic according to claim 5, characterized in that: The filler is a composition of light calcium carbonate and heavy calcium carbonate; the mass ratio of the light calcium carbonate to the heavy calcium carbonate is (28-34): (35-40).

7. The wiring harness mastic according to claim 6, characterized in that: The average particle size of the light calcium carbonate is 1500-2000 mesh; the oil absorption value of the light calcium carbonate is 20-35 mL / 100 g; the average particle size of the heavy calcium carbonate is 1000-1400 mesh.

8. A method for preparing the wiring harness mastic according to any one of claims 1 to 7, characterized in that: The specific steps include: First, stir the functional polyisobutylene and the functional additives in a mixing container at a speed of 100-150 rpm for 30-40 minutes, mix them evenly and set them aside. Then, add all the raw materials except the catalyst into the kneader, heat it to 90-100°C and start kneading for 1-2 hours until there are no particles after kneading, naturally cool it to 60-70°C, add the catalyst and continue kneading for 30-40 minutes to stir evenly, then heat it to 110-120°C and continue kneading for 10-15 minutes. After completion, discharge the material to obtain the wiring harness putty.

Citation Information

Patent Citations

  • Magnetic metal-organic framework material with mesoporous structure and preparation and catalysis reaction thereof

    CN103551196A

  • Micro-crosslinking self-repairing sealant as well as preparation method and application thereof

    CN114456745A